Cell Non-autonomous Proteostasis Regulation in Aging and Disease - Ferreira, Joao Vasco; da Rosa Soares, Ana; Pereira, Paulo (Frontiers in Neuroscience, 2022)
Ageing is a risk factor for a number of diseases, being the more notorious ones perhaps neurodegenerative diseases such as Alzheimer’s and Parkinson’s. These and other age-related pathologies are often associated with accumulation of proteotoxic material inside cells, as well as with the accumulation of protein deposits extracellularly. It is widely accepted that this accumulation of toxic proteins trails a progressive decline in the mechanisms that regulate protein homeostasis, or proteostasis, during ageing. However, despite significant efforts, the progress in terms of novel or improved therapies targeting accumulation of proteotoxic material has been rather limited. For example, clinical trials for new drugs aimed at treating Alzheimer’s disease, by preventing accumulation of toxic proteins, have notoriously failed. On the other hand, it is becoming increasingly apparent that regulation of proteostasis is not a cell autonomous process. In fact, cells rely on complex transcellular networks to maintain tissue and organ homeostasis involving endocrine and paracrine signaling pathways. In this review we will discuss the impact of cell non-autonomous proteostasis mechanisms and their impact in ageing and disease. We will focus on how transcellular proteostasis networks can shed new light into stablished paradigms about the ageing of organisms.